NECESSITY AND IMPORTANCE OF INTER-BUDGETARY RELATIONS BETWEEN THE LINKS OF THE BUDGET SYSTEM - Kimsanbaeva Maftuna Bakhodirovna (Modern American Journals, 2025)
This article highlights the necessity, functional tasks, and economic consequences of inter-budgetary relations between the links of the budget system.
Keywords: Inter-budget transfer, grant, subsidy, budget loan, strong donor regions, weak donor regions, local budget revenues.